(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In order to assess the role of FDI on economic growth,two models were used. The estimation results of the two models are supportedand further analysed by using the relevant econometric techniques viz.Coefficient of determination, standard error, f- ratio, t- statistics, D-WStatistics etc. In the foreign direct investment model , the main determinantsof FDI inflows to India are assessed. The study identified the followingmacroeconomic variables: TradeGDP, R&DGDP, FIN.Position, EXR, andReservesGDP as the main determinants of FDI inflows into India. And therelation of these variables with FDI is specified and analysed in equation . Inorder to study the role of FDI on Indian economy it is imperative to assess thetrend pattern of all the variables used in the determinant analysis. It isobserved that FDI inflows into India shows a steady trend in early nineties butshows a sharp increase after 2005, though it had fluctuated a bit in early2000. However, Gross domestic product shows an increasing trend pattern since1991-92 to 2007-08 (Table 4.2 and Chart - 4.2). Another variable i.e. tradeGDPmaintained a steady trend pattern upto 2001-02, after that it shows acontinuous increasing pattern upto 2008-09. ReservesGDP, another explanatoryvariable shows low trend pattern upto 2000-01 but gained momentum after 2001-02and shows an increasing trend. In addition to these trend patterns of thevariables the study also used the multiple regression analysis to furtherexplain the variations in FDI inflows into India due to the variations causedby these explanatory variables.